Causes of acute poisoning with a fatal outcome in the Republic of Serbia in the period from 2010 to 2018 - Ćirić, Teodora; Baralić, Katarina; Marić, Djurdjica; Javorac, Dragana; Buha Djordjević, Aleksandra; Antonijević Miljaković, Evica; Ćurčić, Marijana; Bulat, Zorica; Antonijević, Biljana; Djukić-Ćosić, Danijela (Archives of Pharmacy, 2022)
The aim of this investigation was to present data analysis on acute poisonings with fatal outcome in the Republic of Serbia in from 2010 to 2018, based on the published Annual reports of the National Poison Control Center of the Military Medical Academy. In the observed 9-year period, the most common cause of acute poisoning was alcohol (50%), followed by drugs (30.1%), while in the third and fourth place were psychoactive substances (7.1%) and gases 4%. Corrosive and pesticide poisoning was present in only 2% of the total number of examined patients per year. The most common reason for the hospitalization was due to drug poisoning (71%), corrosives (9%), pesticides (5%), psychoactive substances (4%), gases (4%) and other pathogens (7%). From 2010 to 2018, number of deaths due to acute poisoning ranged from 26 to 43 annually with an average value of 33. Of 290 deceased patients, 101 (34.9%) were of drug poisoning, 108 (38.5%) corrosives, 28 (9.8%) pesticides, 4 (1.4%) gases, 14 (4.6%) psychoactive substances and 37 (12.4%) other substances, predominantly alcohols and mushrooms. Combination of two or more drugs most often led to death (n=51), while among corrosives, hydrochloric acid was the most common (n=40). Of the pesticides, the most common were organophosphorus insecticides (n=14), while heroin was the most common psychoactive substance (n=7). The analyzed data indicated the importance of preventive measures that need to be carried out in our country to reduce the number of acute poisonings, especially the most severe forms that lead to death.